Twenty Three Aphid Species Νew to the Greek Aphidofauna Caught in Yellow Water Traps in Tobacco Fields - Lykouressis, D.P.; Eastop, V.F.; Katis, N.; Tsitsipis, J.A.; Ntjanis Η. (ENTOMOLOGIA HELLENICA, 1993)
Aphid species abundance was studied by means of yellow Moericke water traps in several tobacco fields in two tobacco growing areas, Aitoloakarnania and Pieria, Greece. In 1992, from alate catches, in three different localities in Aitoloakarnania, a total number of 69, 40 and 31 taxa were caught and identified. Five of them are new records for the Greek aphidofauna. In 1993, from the traps established near Agrinio and in Nea Ephessos, Pieria, a total number of 55 and 139 aphid taxa were caught and identified. Twenty one of them aphid species are new records for Greece of which 3 had been already recorded in the previous year. In total, 23 aphid species recorded for the first time in Greece are presented in this work.